RANCANG BANGUN APLIKASI MODUL PEMBELAJARAN TEKNOLOGI WAN BERBASIS ANDROID - Tio Wiranda; Muhammad Adri (Universitas Negeri Padang, 2019)
Module as medium of learning is one of the ingredients of learning that can be used by students in independent and effective. The learning module application is made with an Android-based platform. WAN technology is one of the subjects for class XI TKJ. This application method was developed using a prototyping model approach with the java programming language using the Android Studio IDE. One of the functions of an android application for students and teachers is the creation of applications related to student learning in which there are learning materials and a collection of practice questions that can be done by students. Android applications that can be developed are e-module applications or learning modules. The results of this thesis is to produce a learning application as a means for learning WAN technology subjects in which there are several menus such as syllabus, lesson plans, modules, video tutorials, options, search and about. The presence of this application is expected to improve students' understanding abilities in learning WAN technology and contribute to learning. Keywords: Android, module, WAN technology, smartphone.